Веселые загадки, поговорки, пословицы, скороговорки - Скворцова С. А. (Сказки-хит, 2010)
Экземпляры: чзд (20150616) / Инвентарный номер: 053923 / Цена: 86.50 / Авт.знак: В 38 / ГРНТИ: 17.82.93 / ББК: 82.3(2)6